Effectiveness of cognitive-behavioral stress management program among novice vocational teachers: a pilot study - Ab Razak, Nurul Husna (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Stress has become one of the major problems that cause the work performance of the novice teachers to decline. The causes of stress including in increasing in sudden of workloads and unfavorable work environment. In order to manage the stress problem, a cognitive-behavioral stress management program is seemed to be one of the best solutions. This program will focusing on controlling information overload, learn the tools to staying calm and in focus despite uncertainty, learn to get more stability and happiness from the areas that they can control, saving time and reducing stress by improved listening, create important time for themselves and reduced stress through improved organization. The target samples will be the first year novice vocational teachers (NVT) because the first year NVT have to cope with so many things to work systematically in a shorter time. Thus, causing the teachers to get high level of stress. NVT will be divided into two groups, where the first group is for control purpose and will not follow up the program while the other group will be sent to the stress management program every two months for six times beginning on January and end on November to see whether this program can help NVT to control stress problems. At the end of the year, the stress level for both groups will be measures to see the effectiveness of the program to control the stress.